Mine spoil restoration: a strategy combining rainwater harvesting and adaptation to random recurrence of droughts in Rajasthan - Pandey, D.N.; Chaubey, A.C.; Gupta, A.K.; Vardhan, H. (2005)
Rajasthan presents evidence for the existence of one of the most advanced examples of ancient mining and accompanied deforestation to be found anywhere in the world. Mining continues to be an important economic activity contributing to 2% of the State Domestic Product and providing at least a 1.76 % share to the regular employment pool in Rajasthan. However, economic benefits of mineral extraction also accompany environmental, economic and social costs. Mine waste dumps and mined out areas viewed simply as the legacies of past may appear overwhelming environmental hazards presenting ugly picture of cultural landscape. However, mine wastes can be transformed into an opportunity for learning, adaptation and productivity enhancement for sustainable livelihoods through ecological restoration. Here the authors propose a strategy for mine spoil restoration aimed at creating a multifunctional ecosystem in mine waste dumps. They suggest that dredging and sediment removal from traditional tanks and ponds can potentially be used to prepare the substratum over the mine wastes for direct seeding. It will also create enhanced decentralized water storage capacity for wildlife and people. Their strategy combines the concomitant revival of traditional water harvesting systems, ground water recharge, enhanced biomass production and an adaptation to random recurrence of droughts in Rajasthan.